Blood flow is required for rapid endothelial cell damage induced by a snake venom hemorrhagic metalloproteinase - Gutiérrez, José María (2006)
The effects of blood flow interruption on the ultrastructural alterations induced by a snake venom hemorrhagic metalloproteinase on skeletal muscle capillary endothelial cells were studied. Saline solution or the metalloproteinase BaP1, from the venom of Bothrops asper, was injected into the gastrocnemius muscles of mice with normal blood flow perfusion or with blood supply abrogated by two different protocols. Tissue was collected 5 min after injection, and both histological and ultrastructural analyses of the muscle capillary vessels were performed. Muscle with normal perfusion injected with saline solution had the typical morphology of normal capillaries, whereas injection of metalloproteinase to muscle with normal blood flow induced prominent degenerative changes in endothelial cells, such as reduction in cell thickness, decrease in the amount of pinocytotic vesicles, prominent distention and rupture leading to extravasation. In contrast, endothelial cells of capillaries from tissue devoid of blood flow and injected with the metalloproteinase did not show degenerative changes. The only alterations observed were a reduction in the capillary lumen and the presence of cytoplasmic projections, or 'pseudopods', both of which were also present in capillaries from tissue devoid of blood flow and injected with saline solution, thus suggesting that such changes are due to the drop in transmural pressure as a consequence of blood flow interruption. Our observations support the hypothesis that biophysical forces operating in the microvasculature, i.e., transmural pressure-dependent wall tension and shear stress, play a significant role in the pathogenesis of endothelial cell damage and hemorrhage induced by snake venom metalloproteinases.